(untitled) (MAUSAM, 1962)
A study has been made of thunderstorms and the occurrence of Ob clouds over Bombay (Santacruz) Airport for the decade 1950 to 1959, statistics have been collected giving the monthly frequency of days of occurrence of thunderstorms in each of the years 1950 to 1959 and also of thunderstorms and thundery conditions (i.e. occurrence of Cb) for the same period, The diurnal distribution of thunderstorm activity, i.e. thundery conditions and of thunderstorms for each of the months has been discussed and the duration of such it activity in each months has been classified. The diurnal distribution of the time of commencement of thunderstorms for each month been tabulated. The synoptic situations connected with typical cases of thunderstorms have been referred to.